(untitled) (Ustozlar uchun, 2026)
Pragmatics plays a vital role in teaching English as a Foreign Language (EFL) because it focuses on how language is used in real communication. While grammar and vocabulary provide the structure of a language, pragmatics explains how meaning is shaped by context, culture, and speaker intention. This paper examines the importance of pragmatic competence, its main components, the challenges teachers face, and effective pedagogical strategies. It also highlights the need for integrating pragmatics into modern communicative language teaching to help learners become more competent and confident users of English in real-life situations.